COGNITIVE REHABILITATION IN ALZHEIMER'S DISEASE: : A SYSTEMATIC REVIEW (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
Alzheimer's disease (AD) involves a combination of genetic and environmental risk factors. Cognitive rehabilitation emerges as a non-pharmacological and alternative method for the treatment of AD, aiming to preserve the independence and daily functioning of this patient. This review aims to collect and map the available information on the effectiveness of cognitive rehabilitation in the treatment of patients with AD in the initial, mild and moderate stages, and is guided by the PRISMA protocol. As a research resource, the following keywords are used: “Alzheimer's disease” AND “cognitive rehabilitation.” There were 259 articles published in the last five years in different databases, seven of which were analyzed in this review. tools for CR interventions were found. Concluding that CR has been effectively contributing to the functional treatment and quality of life of patients affected by AD in early to moderate stages.
Keywords: Alzheimer's disease; Cognitive Rehabilitation; Intervention